Granulab: commercializing GranuMas - Said, Mohd Fuaad; Adham, Khairul Akmaliah; Muhamad, Nursaadah; Md. Ramli, Raudha (Universiti Putra Malaysia Press, 2013)
GranuLab Sdn. Bhd. (GranuLab) was formed in 2005 to host the development and commercialization of a patented synthetic bone graft substitute, made from limestone and pure chemicals, called GranuMaS. The GranuMaS technology was invented by a group of researchers, led by one from SIRIM. The research began in 2000, and in 2005, GranuLab founders identified a huge business opportunity for GranuMaS. They then developed the business opportunity, resulting in the transfer of GranuMaS technology to GranuLab, and in turn GranuLab being acquired by Sindora in mid-2007. By then, the founders had to think of its next course of action. But, they realized the need to first educate GranuLab’s parent company on managing a technology-based venture, particularly one that involved an invasive medical technology. This case describes the process of innovation of the medical technology, technology transfer, and entrepreneurship at GranuLab, leading to the commercialization of GranuMaS. It is designed to stimulate critical thinking of the process of innovation and entrepreneurship, and provide understanding of the process of a medical technology commercialization.